2016
DOI: 10.1055/s-0042-118598
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Errors of 35 Weight Estimation Formulae in a Standard Collective

Abstract: The estimation of foetal weight is an integral part of prenatal care and obstetric routine. In spite of its known susceptibility to errors in cases of underweight or overweight babies, important obstetric decisions depend on it. In the present contribution we have examined the accuracy and error distribution of 35 weight estimation formulae within the normal weight range of 2500-4000 g. The aim of the study was to identify the weight estimation formulae with the best possible correspondence to the requirements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
4
2
2
Order By: Relevance
“…In our study, estimation of fetal weight with Campbell, Combs and Ott formulae have a tendency to underestimate fetal weight, other 8 formulae overestimate fetal weight. These results contrast with Hoopmann et al study [17], where the majority of the tested formulae gave underestimations of the actual birth weight. Analysis of 3D formulas [5] shows higher accuracy of 3D Schild formula compared to Hadlock4 in group of fetuses between 2500g and 3000g (mean absolute percentage error 5.3% vs 7.8%) and those between 3500 g and 4000 g (4.8% vs 9.6%).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In our study, estimation of fetal weight with Campbell, Combs and Ott formulae have a tendency to underestimate fetal weight, other 8 formulae overestimate fetal weight. These results contrast with Hoopmann et al study [17], where the majority of the tested formulae gave underestimations of the actual birth weight. Analysis of 3D formulas [5] shows higher accuracy of 3D Schild formula compared to Hadlock4 in group of fetuses between 2500g and 3000g (mean absolute percentage error 5.3% vs 7.8%) and those between 3500 g and 4000 g (4.8% vs 9.6%).…”
Section: Discussioncontrasting
confidence: 90%
“…Although, the highest Spearman correlations belong to Hadlock formulas. Hoopmann et al [17] compared 35 formulae in 3416 fetuses with weight between 2500 g and 4000 g. They determined and compared the mean percentage error, the mean absolute percentage error, also the proportions of estimates within the error ranges of 5, 10, 20 and 30 %. In addition, separate regression lines were calculated for the relationship between estimated and actual birth weight.. Halaska formula had the best value of mean absolute percentage error (6.6%).…”
Section: Discussionmentioning
confidence: 99%
“…As Kehl et al already stated in 2012 [34], "weight estimation with conventional biometric parameters by 2D ultrasound has reached its limits". To use the existing formulas more effectively, some authors have favored a "two-step procedure" for fetal weight estimation [35]. In such an approach, in a first step, the weight range is delineated by one or more sonographic parameters (e.g., AC).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with a more recent formula (INTERGROWTH‐21), the Hadlock I formula showed a significantly lower MAPE . A recently published trial showed that the Hadlock models reached the lowest MAPEs in 20 weight estimation formulas evaluated in a large population of nearly 3500 fetuses weighing between 2500 and 4000 g in a standard study population . There have been divergent views regarding the accuracy of the EFW in relation to the number of parameters included.…”
Section: Methodsmentioning
confidence: 99%
“…For fetuses in the upper weight range, the formula of Merz et al was included, as it has been shown in several previous studies that this formula is more appropriate for these fetuses . Fetal weight estimation is more precise for male fetuses, and using sex‐specific weight estimation formulas can improve the accuracy of the estimates .…”
Section: Methodsmentioning
confidence: 99%